Inhibitors against Fungal Cell Wall Remodeling Enzymes. (12th December 2017) - Delso, Ignacio; Valero‐Gonzalez, Jessika; Gomollón‐Bel, Fernando; Castro‐López, Jorge; Fang, Wenxia; Navratilova, Iva; van Aalten, Daan M. F.; Tejero, Tomás; Merino, Pedro; Hurtado‐Guerrero, Ramon
Abstract: Fungal β‐1, 3‐glucan glucanosyltransferases are glucan‐remodeling enzymes that play important roles in cell wall integrity, and are essential for the viability of pathogenic fungi and yeasts. As such, they are considered possible drug targets, although inhibitors of this class of enzymes have not yet been reported. Herein we report a multidisciplinary approach based on a structure‐guided design using a highly conserved transglycosylase from Sacharomyces cerevisiae, that leads to carbohydrate derivatives with high affinity for Aspergillus fumigatus Gel4. We demonstrate by X‐ray crystallography that the compounds bind in the active site of Gas2/Gel4 and interact with the catalytic machinery. The topological analysis of noncovalent interactions demonstrates that the combination of a triazole with positively charged aromatic moieties are important for optimal interactions with Gas2/Gel4 through unusual pyridinium cation–π and face‐to‐face π–π interactions. The lead compound is capable of inhibiting Af Gel4 with an IC50 value of 42 μm . Abstract : Structure‐guided design using a transglycosylase from Saccharomyces cerevisiae as a model led to a micromolar inhibitor of pathogenic Aspergillus fumigatus . X‐ray crystallography studies show that the compounds in this series bind in the active site of Gas2/Gel4 transglycosylase and interact with the enzyme′s catalytic machinery.